Can reliable values of Young's modulus be deduced from Fisher's (1971) spinning lens measurements? - Burd, H; Wilde, G; Judge, S (2006)
The current textbook view of the causes of presbyopia rests very largely on a series of experiments reported by R.F. Fisher some three decades ago, and in particular on the values of lens Young's modulus inferred from the deformation caused by spinning excised lenses about their optical axis (Fisher 1971) We studied the extent to which inferred values of Young's modulus are influenced by assumptions inherent in the mathematical procedures used by Fisher to interpret the test and we investigated several alternative interpretation methods. The results suggest that modelling assumptions inherent in Fisher's original method may have led to systematic errors in the determination of the Young's modulus of the cortex and nucleus. Fisher's conclusion that the cortex is stiffer than the nucleus, particularly in middle age, may be an artefact associated with these systematic errors. Moreover, none of the models we explored are able to account for Fisher's claim that the removal of the capsule has only a modest effect on the deformations induced in the spinning lens.